2021
DOI: 10.1123/ijspp.2020-0692
|View full text |Cite
|
Sign up to set email alerts
|

Dose–Response Relationship Between Velocity Loss During Resistance Training and Changes in the Squat Force–Velocity Relationship

Abstract: Purpose: This study aimed to compare the adaptations provoked by various velocity loss (VL) thresholds used in resistance training on the squat force–velocity (F–V) relationship. Methods: Sixty-four resistance-trained young men were randomly assigned to one of four 8-week resistance training programs (all 70%–85% 1-repetition maximum) using different VL thresholds (VL0 = 0%, VL10 = 10%, VL20 = 20%, and VL40 = 40%) in the squat exercise. The F–V relationship was assessed under unloaded and loaded conditions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…In contrast, a previous study involving light‐load plyometric exercise (using a trampoline training device) in older adults has shown meaningful increases in VL FL and VL PA (+8 and +7%, respectively) 13 . The discrepancies between studies may derive from differences in the training device used and some methodological limitations in determining this measure in our study (with large portions of fascicle length lying outside the available field‐of‐view) potentially introducing bias 49 . While it is possible that LL‐PT (which resembles plyometric exercise to a certain extent) would benefit the effectiveness of the stretch‐shortening cycle, it remains to be explored whether LL‐PT or HL‐PT would have greater adaptive potential in this regard.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In contrast, a previous study involving light‐load plyometric exercise (using a trampoline training device) in older adults has shown meaningful increases in VL FL and VL PA (+8 and +7%, respectively) 13 . The discrepancies between studies may derive from differences in the training device used and some methodological limitations in determining this measure in our study (with large portions of fascicle length lying outside the available field‐of‐view) potentially introducing bias 49 . While it is possible that LL‐PT (which resembles plyometric exercise to a certain extent) would benefit the effectiveness of the stretch‐shortening cycle, it remains to be explored whether LL‐PT or HL‐PT would have greater adaptive potential in this regard.…”
Section: Discussioncontrasting
confidence: 62%
“…13 The discrepancies between studies may derive from differences in the training device used and some methodological limitations in determining this measure in our study (with large portions of fascicle length lying outside the available field-of-view) potentially introducing bias. 49 While it is possible that LL-PT (which resembles plyometric exercise to a certain extent) would benefit the effectiveness of the stretch-shortening cycle, it remains to be explored whether LL-PT or HL-PT would have greater adaptive potential in this regard. Some limitations should be considered when interpreting the present findings.…”
Section: T a B L E 1 Mechanical Characteristics Of Light-load And Hea...mentioning
confidence: 99%
“…Two studies [ 64 , 65 ] used a linear encoder that was not, to our knowledge, validated in the peer-reviewed literature whereas all other studies used valid and reliable methods, equipment, or instruments to evaluate their outcomes of interest. Fourteen studies [ 18 , 25 , 26 , 42 45 , 60 , 61 , 70 , 73 , 77 79 ] were at a high risk of bias for not having a familiarization session. Four studies [ 69 , 75 , 76 , 80 ] did not provide sufficient information regarding their familiarization sessions and hence, had an unclear risk of bias The rest of the studies provided sufficient information about familiarization session procedures or specifically stated that all participants were accustomed to the study protocols (i.e., performed them in the past).…”
Section: Resultsmentioning
confidence: 99%
“…5 b). The authors from the several studies [ 25 27 , 60 ] suggested that an inverted U-shaped relationship might exist between VL experienced in a set and maximal strength gains. For instance, Pareja-Blanco et al [ 25 , 26 ] reported that once a moderate VL threshold was exceeded (e.g., 20 or 25% VL), further increases in strength gains were not observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation